British responses to Du Bartas' Semaines, 1584-1641 - Auger, P (2012)
The reception of the Huguenot poet Guillaume de Saluste Du Bartas' Semaines (1578, 1584 et seq.) is an important episode in early modern literary history for understanding relations between Scottish, English and French literature, interactions between contemporary reading and writing practices, and developments in divine poetry. This thesis surveys translations (Part I), allusions and quotations in prose (Part II) and verse imitations (Part III) from the period when English translations of the Semaines were being printed in order to identify historical trends in how readers absorbed and adapted the poems. Early translations show that the Semaines quickly acquired political and diplomatic affiliations, particularly at the Jacobean Scottish Court, which persisted in subsequent decades (Chapter 1). William Scott's treatise The Model of Poesy (c. 1599) and translations indicate how attractive the Semaines' combination of humanist learning and sacred rhetoric was, but the poems' potential appeal was only realized once Josuah Sylvester's Devine Weeks (1605 et seq.) finally made the complete work available in English (Chapter 2). Different communities of readers developed in early modern England and Scotland once this edition became available (Chapter 3), and we can observe how individuals marked, copied out, quoted and appropriated passages from their copies of the poems in ways dependent on textual and authorial circumstances (Chapter 4). The Semaines, both in French and in Sylvester's translation, were used as a stylistic model in late-Elizabethan playtexts and Zachary Boyd's Zions Flowers (Chapter 5), and inspired Jacobean poems that help us to assess Du Bartas' influence on early modern poetry (Chapter 6). The great variety of responses to the Semaines demonstrates new ways that intertextuality was a constituent feature of vernacular religious literature that was being read and written in sixteenth- and seventeenth-century Britain.